Molecular detection of Ehrlichia canis in dogs from three districts in Punjab (Pakistan). Issue 2 (7th February 2018) - Malik, Muhammad I.; Qamar, Muhammad; Ain, Quratul; Hussain, Malik F.; Dahmani, Mustapha; Ayaz, Mazhar; Mahmood, Asim K.; Davoust, Bernard; Shaikh, Rehan S.; Iqbal, Furhan
Abstract: Canine monocytic ehrlichiosis is a tick‐borne disease caused by an intracellular alpha‐proteobacterium, Ehrlichia canis, which replicates within mononuclear cells in the host. This study was designed to use a polymerase chain reaction (PCR) protocol for the molecular detection of E. canis by the amplification of a portion of its 16S rRNA gene, as well as the effects of this alpha‐proteobacterium on the haematological parameters of the sampled dogs and the risk factors associated with E. canis infection. A total of 151 blood samples were collected from dogs of various breeds at three sampling sites (Lahore, Rawalpindi/Islamabad and Multan) in Punjab, Pakistan. Data regarding the epidemiological factors (including age, gender, breed, body temperature, deworming, vaccination, mucous membrane status, hydration status, the presence of haematuria and tick infestation) were collected through a questionnaire at the time of sample collection. A 400 bp DNA fragment of the 16S rRNA gene of E. canis was amplified from 42 dog blood samples (28% of the total), [Lahore ( N = 24), Rawalpindi/Islamabad ( N = 13) and Multan ( N = 05)] through PCR. Data analysis revealed that the character of the animals (age, sex and breed) had no significant association ( P > 0.05) with the presence of E. canis . Various haematological parameters were also compared, and the results revealed that all of the parameters remained unaffected, except significantly lower white blood cell counts ( P = 0.004) in E. canis ‐positive blood samples, as compared with the control group. We concluded that this is the first molecular confirmation of canine infection by E. canis using PCR. Moreover, no specific epidemiological parameter was found associated with the prevalence of E. canis in dogs. Abstract : The is the first Ehrlichia canis detection report in dogs from Pakistan. Significant reduction in the white blood cell count was observed in E. canis ‐positive dogs.